2021
DOI: 10.1101/2021.04.19.440086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large scale discovery of coronavirus-host factor protein interaction motifs reveals SARS-CoV-2 specific mechanisms and vulnerabilities

Abstract: Viral proteins make extensive use of short peptide interaction motifs to hijack cellular host factors. However, most current large-scale methods do not identify this important class of protein-protein interactions. Uncovering peptide mediated interactions provides both a molecular understanding of viral interactions with their host and the foundation for developing novel antiviral reagents. Here we describe a scalable viral peptide discovery approach covering 229 RNA viruses that provides high resolution infor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 69 publications
1
44
1
Order By: Relevance
“…Most of the overlapping hits were present in AP-MS studies and involved in ribosome biogenesis and RNA process (for example FBL, BMS1, NOP56, BOP1, WDR12, DHX37 and DDX54) and immune response (for example, MOV10, EIF2AK2, TARBP2, TRIM25, HERC5 and ZCCHC3) (Table S3). It is important to note that two stress granule proteins, G3BP1 and G3BP2, were most consistently identified in other studies [4][5][6][7][8]15,[26][27][28][29]. G3BP1 and G3BP2 are downregulated during SARS-CoV-2 infection, and inhibition of stress granule formation by the N protein indicates that the N protein is involved in suppressing the host immune response to favour virus replication [5,30].…”
Section: Comparison Of the N Protein Interactome With Other Sars-cov-2-induced Proteomes And Transcriptomesmentioning
confidence: 74%
“…Most of the overlapping hits were present in AP-MS studies and involved in ribosome biogenesis and RNA process (for example FBL, BMS1, NOP56, BOP1, WDR12, DHX37 and DDX54) and immune response (for example, MOV10, EIF2AK2, TARBP2, TRIM25, HERC5 and ZCCHC3) (Table S3). It is important to note that two stress granule proteins, G3BP1 and G3BP2, were most consistently identified in other studies [4][5][6][7][8]15,[26][27][28][29]. G3BP1 and G3BP2 are downregulated during SARS-CoV-2 infection, and inhibition of stress granule formation by the N protein indicates that the N protein is involved in suppressing the host immune response to favour virus replication [5,30].…”
Section: Comparison Of the N Protein Interactome With Other Sars-cov-2-induced Proteomes And Transcriptomesmentioning
confidence: 74%
“…Next, we studied another factor known to be associated with conservation – gene expression level, by calculating the average transcript expression level across human tissues using the human protein atlas database 18 . We observed that PRD proteins in general, and their subset that binds viral proteins in particular, tend to be more highly expressed across tissues in comparison with other groups of proteins (FDR-corrected P-value = 4.22×10 −10 and 2.92×10 − 91 , respectively, Mann-Whitney test, Fig 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…These short and simple motifs can readily evolve in viral proteins to facilitate the formation of interactions with host proteins through domain-motif interactions mimicking within-host interactions and displacing them [11][12][13] . Literature-based surveys 14,15 and proteome-wide analyses 16,17 suggested that ELMs are found in a diverse set of viruses and can participate in many stages of viral replication (see for example Despite their simplicity, ELMs can form complex regulatory modules that enable efficient perturbation of cellular networks 16,18 . For example, a PDZ-binding motif at the terminus of the E6 oncoprotein in cancer-causing papillomaviruses enables interaction with PDZ domains of several human signaling proteins, supporting cell transformation 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,41 More recent work characterizing viral-host interaction motifs has uncovered a conserved G3BP-binding motif, ΦxFG (where Φ is a hydrophobic residue). 42 This G3BP interaction motif is present in both viral and host proteins, such as the cellular SG protein and known G3BP interactor USP10, and is remarkably similar to the alphavirus nsP3-G3BP interaction motif, FGDF, but likely binds with lower affinity. 42 Moreover, TRIM25 was identified as a G3BP1 interaction partner.…”
Section: Substrate Trapping Approach Enriches For Novel Trim25 Intera...mentioning
confidence: 98%